Unpacking the Group Engagement Model Within a Police Department: Peers, Legitimacy, and Unintended Consequences - Sarpong, Dennis (Criminal justice and behavior, 2025)
The group engagement model (GEM) suggests that a fair internal climate within police departments enhances officer support for fair policing. However, prior work has not considered the role of peers in creating a fair climate, the theoretical positioning of legitimacy perceptions, and the possible unintended effects of internal fairness. Active-duty officers (n = 292) completed a survey measuring their perceptions of peer and supervisor procedural justice, distributive justice, police identification, legitimacy of both command and supervisors and support for procedurally just policing and intrusive policing. The results showed that peer procedural justice was associated with both support for procedurally just policing and intrusive policing. The implications of the result are discussed in terms of the role of peers in a fair internal climate and the potential for a fair climate to have unanticipated effects on officers’ support for various policing strategies.